Implikasi Citra Merek dalam Pemasaran Lembaga Pendidikan Islam Terhadap Hasil Rekrutmen Peserta Didik - Harisatunisa Harisatunisa; Lulu Mahyanal Izza; Dwi Lestari; Anisa Fitriana; Farah Istiqorini (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2021)
Higher number of students recruitment in Islamic Education Institutions is one indicator of an institution quality. Islamic educational institutions are currently required to be able to promote their institutions to expand the students’ recruitment. This paper aims to describe the implication of brand image in the promotion of Islamic educational institutions on student recruitment. The method used in this paper is literature review. Books, articles, websites, laws relating to brand image, brand management, higher education and marketing management are collected, read, compared, and analyzed to identify the roles of brand image in promoting the Islamic educational institutions. The results of this study indicate that there are three implications of brand image in the promotion of Islamic educational institutions on student recruitment: brand image is strengthening the position of Islamic educational institutions, brand image is illustrating the effectiveness of the institution, and the brand image can be used as a reference in designing the institution identity.